Pengaruh Penggunaan Media Digital Terhadap Kemampuan Berbahasa Daerah Siswa Wilayah Papua Daerah Sorong - Ramadhan, muthahhir; Nabil Abdul Haji Pelu; Hafiz Irwandi; Wardah Luthfi Yahtul Rahmah; Putri Nurmiati Adiadam; Janai Kuya (El-Tarbawi : Jurnal Pendidikan Islam dan Humaniora, 2026)
Regional languages are an important part of cultural identity and serve as a medium for transmitting knowledge across generations. However, the development of digital media has changed communication patterns among younger generations and may affect the sustainability of regional language use. This study falls within the scope of sociolinguistics and education and aims to analyze the influence of digital media use on students’ regional language proficiency in Sorong, Southwest Papua, and to identify factors affecting the use of regional languages in daily life. This study employed a qualitative approach using a case study design. The research participants consisted of elementary, junior high, and senior high school students from Indigenous Papuan communities, supported by six teachers and four parents as additional informants. Data were collected through semi-structured in-depth interviews and document analysis of relevant sources published within the last five years. Data analysis followed the interactive model of Miles, Huberman, and Saldana, including data condensation, data display, and conclusion drawing and verification. The study indicates that digital media use may influence the frequency of regional language use and strengthen the dominance of Indonesian in students’ communication. Nevertheless, digital media also has potential to support regional language revitalization when utilized adaptively and oriented toward local language preservation.